Effectiveness of Management Strategy of Implementation of Stunting Program: Case Study - Abdilah Irsyad; Dwiyani Sudaryanti; Siti Asiyah (Indonesian Journal of Global Health Research, 2025)
Stunting remains a significant public health challenge in Indonesia, with multifactorial causes including maternal nutrition, inadequate infant feeding practices, and poor sanitation. Effective implementation management of stunting programs is key to addressing this issue sustainably. This study aimed to analyze the effectiveness of management strategies in implementing stunting reduction programs in Tempeh Subdistrict, Lumajang Regency, focusing on process and outcome indicators. The qualitative approach employed a purposive sampling method, consisting of six informants divided into primary informants and triangulation informants. These included health office staff, community health center officers, and mothers of stunted children. Data were collected through interviews and document reviews, then analyzed using interactive data condensation, presentation, and conclusion drawing. The study found that the SIDERA program (Stimulation, Early Detection Friendly to Children) empowered PAUD teachers in early detection and parental education on nutrition, which contributed to reduced wasting and underweight prevalence, indicators closely linked to future stunting. Effective cross-sectoral synergy among health centers, local governments, educational institutions, and community health volunteers facilitated program implementation. However, challenges remain in timely training delivery and strategic targeting of interventions to the most affected communities. Effective management strategies that emphasize comprehensive understanding of programs, accurate targeting, timeliness, achievement of objectives, and tangible changes in community behavior are crucial for stunting prevention efforts. Strengthening coordination and optimizing training schedules for key stakeholders such as PAUD teachers can further improve program outcomes.